Cement–paperboard composite for speaker/woofer casing: Experimental trend analysis (ETA) and performance evaluation. Issue 1 (1st January 2021) - Adesoji, Adediran Adeolu; Adewale, Akinwande Abayomi; Balogun, Oluwatosin Abiodun; Adesina, Olanrewaju Seun; Ademati, Akeem Oladele; Akeju, Emmanuel A.; Mahamood, Rasheedat M.; Akinlabi, Esther Titilayo
Abstract: One of the uses of particle board is in the design of speaker/woofer casing, but with increasing demand, the cost is skyrocketing, effects of which lead to the high cost of end-use woofer gadgets. Cement–paper composite reinforced with snail shell powder/banana fiber was developed as an alternative. The fiber was grouped into two; untreated banana fiber (UBF) and treated banana fiber (TBF) (treated with 1 M NaOH). Fibers were infused into the composite at 0%, 0.5%, 1%, 1.5%, 2%, and 2.5% by weight of paper pulp while snail shell powder was added at 15 wt.% constant proportion for all samples produced. Curing was carried out for 28 and 56 days, respectively. The composite boards produced were examined for physical, mechanical, and microstructural properties. Results obtained indicated an uptrend in water absorption and thickness swelling at increasing fiber loading. Internal bond strength, screw holding strength, moduli of rupture, and elasticity were observed to be enhanced with increment in fiber proportion. It was further noticed that alkaline TBF performed better than the untreated fiber, hence recommended for paperboard production. Experimental trend and performance analysis engaged in revealed hydration to be the most efficient experimental variable and important for overall property maximization in cement–paper composite. Performance evaluation conducted showed effective property index was noticed to be highest for composite board doped with 2.5 wt.% TBF.